Effects of Trauma in Adulthood and Adolescence on Fear Extinction and Extinction Retention: Advancing Animal Models of Posttraumatic Stress Disorder - Chen, Chieh V.; Chaby, Lauren E.; Nazeer, Sahana; Liberzon, Israel (Frontiers in Behavioral Neuroscience, 2018)
Evidence for and against adolescent vulnerability to posttraumatic stress disorder (PTSD) is mounting, but this evidence is largely qualitative, retrospective, or complicated by variation in prior stress exposure and trauma context. Here, we examine the effects of development on trauma vulnerability using adult and adolescent (early and mid adolescence) rats and two types of trauma: an established animal model of PTSD, single prolonged stress (SPS), and a novel composite model - single prolonged stress-predation version (SPSp). We demonstrate for the first time that early and mid adolescent rats are capable of fear and safety learning, as well as the retention of safety learning. Our results also demonstrate that both types of trauma attenuated the retention of safety learning (fear extinction), a hallmark of PTSD-like phenotype after trauma in adulthood, but not after early or mid adolescence trauma, suggesting that adolescence might convey resilience to SPS and SPSp traumas. Across all three life stages, the effects of SPS exposure and a novel predation trauma model, SPSp, had similar effects on behavior suggesting that trauma type did not affect the likelihood of developing PTSD-like symptoms, and that the predation-based trauma model may have convergent validity with SPS, a prominent model of behavioral, physiological, and neurological PTSD symptomatology.